A case study of the dynamics of scaffolding among ESL learners and online resources in collaborative learning. Issue 1 (17th February 2017) - Hsieh, Yi Chin
ABSTRACT: Collaborative learning has been widely applied in education, and has been seen as conducive to student learning. The advent of technology and its applications in education have also greatly enhanced the classroom learning environment, leading to increasing research attention on the combination of technology and collaboration. The case study discussed in this article explores collaborating learners' patterns of interaction in an Internet-enhanced, face-to-face collaborative setting by investigating learners' interactions with peers and online resources. Four graduate-level ESL learners (three Taiwanese and one Japanese) worked in pairs to write an essay with the support of online resources. The construct of high quality collaboration was used to examine learners' interaction patterns. Three distinctive scaffolding patterns among learners and online resources were identified: (1) peer-to-peer scaffolding, (2) multi-directional scaffolding, and (3) individual scaffolding. The findings suggest that online resources can facilitate critical scaffolding in learners' interaction and knowledge construction, which also encourages collaborative learner autonomy. The proficiency gap between collaborating learners was also observed to be alleviated through the support of online resources for the less proficient peers. This study sheds light on the role online resources can play in collaborative language learning.